A DISCOURSE ANALYSIS OF ARTICLES APPEALING FOR ENVIRONMENTAL PROTECTION IN ENGLISH AND VIETNAMESE ELECTRONIC NEWSPAPERS - Đỗ Thị Hội An; Nguyen Thi Quynh Hoa Ph.D huong dan (2014)
Introduction - Literature review and theoretical background - Methods and procedure....
Master thesis in social sciences and humanities.
Keywords: Đỗ Thị Hội An, A DISCOURSE ANALYSIS OF ARTICLES APPEALING FOR ENVIRONMENTAL PROTECTION IN ENGLISH AND VIETNAMESE ELECTRONIC NEWSPAPERS, NEWSPAPERS, ENVIRONMENTAL